2017
DOI: 10.1515/arls-2017-0008
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Production and Culling Rate With Regard to the Profitability in a Dairy Herd

Abstract: As milk prices move away from production costs, dairy farms are under increased pressure to find ways to protect profitability on the farm. Producers have some problems that they can improve. Improve the milk production, produce more milk to sell focused on quality (reduce the amount of high level of somatic cell count). The deterioration of animal health status (lameness, mastitis and different metabolic disorders) can have a serious impact on cow productivity, causing pain and discomfort, production losses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…Furthermore, the dairy farm-workers’ correct perception about the influence of poor milk yield and mastitis on culling of dairy cows resembles previous reports which noted milk yield losses as a risk factor for culling dairy cows (Orpin and Esslemont 2016 ; Horváth et al 2017 ; Kerslake et al 2018 ). Mastitis directly influences milk production in dairy farms and also increases production costs (Harmon 1994 ).…”
Section: Discussionsupporting
confidence: 70%
“…Furthermore, the dairy farm-workers’ correct perception about the influence of poor milk yield and mastitis on culling of dairy cows resembles previous reports which noted milk yield losses as a risk factor for culling dairy cows (Orpin and Esslemont 2016 ; Horváth et al 2017 ; Kerslake et al 2018 ). Mastitis directly influences milk production in dairy farms and also increases production costs (Harmon 1994 ).…”
Section: Discussionsupporting
confidence: 70%
“…Milk yield per cow is one of the main factors influencing the economics of dairy cattle production (Nemeckova et al 2015;Krpalkova et al 2016). High milk yields mean high incomes but might also contribute to poorer cow health and fertility and, as a result, to increased culling rate (Horvath et al 2017a). The profitability of dairy farms also depends greatly on the reproductive efficiency of dairy cows and the optimal length of the calving interval (Dono et al 2013).…”
mentioning
confidence: 99%
“…0.13 and 0.09, respectively. As Horvath et al (2017) demonstrated, the duration of lactation may determine the frequency of culling, as an increase in its length is accompanied by an increase in the percentage of cows culled due to reproductive disorders. The present study has shown no statistically significant differences in the duration of lactation, which ranged from 262 (genotype CT) to 272 (genotype CC) days.…”
Section: Discussionmentioning
confidence: 99%
“…This is confirmed by findings presented by other authors (Brickell and Wathes 2011;Litwinczuk et al 2016;De Vries and Marcondes 2020), who demonstrate that the actual length of cow productive life has been shorter than the natural lifespan in recent years. Brickell and Wathes (2011) demonstrated that 43% of cows were culled before the third calving, and Horvath et al (2017) showed that as many as 26% of cows were culled during the first lactation. The productive life of cows in the herd should span from five to eight lactations, which indicates that the cows from the analysed herd were culled too early, as the average number of lactations ranged from 3.78 to 4.31 (in the animals with genotypes TT and CC, respectively).…”
Section: Discussionmentioning
confidence: 99%